The European Electricity Market: Centralization of Regulation or Competition between Regulatory Approaches? - Lars Kumkar (Institut für Weltwirtschaft (IfW), 2002)
The European Council and the European Parliament adopted the European Electricity Directive in 1996. Since the end of the implementation period in 1999, some parts of the European power sector have been liberalized. In most countries, e.g., in Germany, price reductions and comprehensive institutional changes, e.g., cross-border mergers and the establishment of new power exchanges, are on the agenda. The data for cross-border electricity trade and for price developments indicate the emergence of an internal European market for electricity following the implementation of the Electricity Directive. Even if it is highly questionable whether a completely integrated internal market already exists, the obvious evolution towards more competition and market integration does not seem stoppable anymore. The Electricity Directive of 1996 is unambiguously a success on the way to competition in the European electricity industry. On March 13, 2001, merely two years after the end of the Directive's implementation period, the European Commission presented far-reaching proposals for further steps. On the one hand, these proposals aim at an acceleration of the quantitative market opening. On the other hand, they contain a far-reaching revision of the existing Electricity Directive: The proposals would induce a Europewide harmonization of the substantive as well as the institutional design of regulatory policies. This holds both for the network-use model and for public service objectives. According to the Commission's proposals of March 2001, the member states would be obliged to establish independent regulatory authorities. In Germany, for example, this could result in a sector- specific regulation authority for electricity in addition to the already existing telecommunications authority and the competition authorities. Considering the technical characteristics of the electricity industry and the recent experiences with electricity market liberalization leads to a quite simple normative conclusion: the competence assignment should give maximum leeway for competition between different regulatory approaches, and, therefore, for more or less spatially restricted experiments. The goal must be to choose regulatory institutions that provide for competition between alternative approaches and allow ongoing improvements. Thus, there is a strong argument against the noticeable competence reassignment from the EU member states to the European level as proposed by the Commission. Recognizing the disadvantages of a far-reaching harmonization of regulatory policies, one need not regret that the Council of Gothenborg in June 2001 and the Council of Barcelona in 2002 did not reach definitive decisions on the Commission's proposals of March 2001. This “reprieve” should be used for an intensive discussion about a proper competence assignment between the EU and the member states.
Keywords: 330; Elektrizitätspolitik; EU-Binnenmarkt; Elektrizitätswirtschaft; Netzzugang; Zentralstaat; Institutioneller Wettbewerb; Markteintritt; EU-Staaten